Smartphone and tablet apps for concussion road warriors (team clinicians): a systematic review for practical users - Lee, H.; Sullivan, S. J.; Schneiders, A. G.; Ahmed, O. H.; Balasundaram, A. P.; Williams, D.; Meeuwisse, W. H.; McCrory, P. (British Journal of Sports Medicine, 2015)
Background: Mobile technologies are steadily replacing traditional assessment approaches for the recognition and assessment of a sports concussion. Their ease of access, while facilitating the early identification of a concussion, also raises issues regarding the content of the applications (apps) and their suitability for different user groups. Aim: To locate and review apps that assist in the recognition and assessment of a sports concussion and to assess their content with respect to that of internationally accepted best-practice instruments. Methods: A search of international app stores and of the web using key terms such as `concussion`, `sports concussion` and variants was conducted. For those apps meeting the inclusion criteria, data were extracted on the platform, intended users and price. The content of each app was benchmarked to the Sport Concussion Assessment Tool 2 (SCAT2) and Pocket SCAT2 using a custom scoring scheme to generate a percentage compliance statistic. Results: 18 of the 155 apps identified met the inclusion criteria. Almost all (16/18) were available on an iOS platform and only five required a payment to purchase. The apps were marketed for a wide range of intended users from medical professionals to the general public. The content of the apps varied from 0% to 100% compliance with the selected standard, and `symptom evaluation` components demonstrated the highest level of compliance. Conclusions: The surge in availability of apps in an unregulated market raises concerns as to the appropriateness of their content for different groups of end users. The consolidation of best-practice concussion instruments now provides a framework to inform the development of future apps.